PERLINDUNGAN HUKUM TERHADAP HAK BURUH WANITA HAMIL MENURUT UU NO. 13 TAHUN 2003 TENTANG KETENAGAKERJAAN (CONTOH KASUS: PT X) - Siti Syarah Armanida; Andari Yurikosari (Fakultas Hukum Universitas Tarumanagara, 2020)
A woman is guaranteed the right to return to the same position after her maternity leave. The need for legal protection for women workers who are pregnant but not treated properly and get rights in accordance with the provisions in the Manpower Act. The formulation of the problem in this study is how the legal protection for pregnant women workers who work at PT X based on the law and how to resolve violations of the law that occurs in pregnant women workers who work at PT X. The method used in this study is normative legal research. Labor Law. Suggestions in this thesis are to the government through Parliament to immediately revise the Article in the Manpower Act concerning criminal and administrative sanctions that regulate violations of labor rights that do not get wages from maternity leave or miscarriage leave. Furthermore, workers, especially women, must be more careful in signing agreements to work together, whether their rights have been fulfilled in the agreement or not, in accordance with applicable regulations